Mecanismos de prevención de la violencia contra la mujer en los barrios de las parroquias el Valle y Carigán cantón Loja, en la actualidad - Arias Tapia, Rosa Dalila (2024)
The research that was established in this work in academic function has the functionality of addressing the existing mechanisms to prevent gender violence, specifically in women, the study is focused on the communities of Valle and Cárigan, two parishes belonging to the city of Loja. The main objective of the research is to identify and evaluate the risk factors along with the mechanisms that currently exist to prevent this phenomenon in order to establish improvements. For this reason, it has been taken into consideration to make use of the mixed methodology, using instruments such as interviews and surveys aimed at the residents of both localities, to complete the study an exhaustive documentary and political review of the sector was carried out. Through the implementation of this technique, it was obtained as a result that the psychosocial factors that are most prevalent in both sectors are stress and lack of social support, which brings with it that security and livelihoods are affected by the prevalence of these psychosocial factors, therefore, it is considered relevant to promote more education where it emphasizes how harmful the increase in violence is and so on. identify the psychosocial factors that influence this phenomenon. It can be seen in the tabulation that 41% of those surveyed consider that violence is daily, and in turn, 56.76% do not feel safe in their neighborhood. Similarly, among the most common forms of abuse, 90.5% know more about psychological violence, while 86.5% physical and, finally, 63.5% sexual. In the implementation of the conclusions, it is suggested to improve the situation of the sector since it is crucial that the community support network be strengthened, in the same way programs should be implemented where training and monitoring mechanisms are established and that their evaluation is continuous. The research emphasizes the importance of adopting a comprehensive and collaborative approach that includes all social actors to create a fairer and safer environment for women.